Recommendations for the surveillance of mental health problems in childhood, adolescent, and young adult cancer survivors: a report from the International Late Effects of Childhood Cancer Guideline Harmonization Group. Issue 4 (April 2022) - Marchak, Jordan Gilleland; Christen, Salome; Mulder, Renée L; Baust, Katja; Blom, Johanna M C; Brinkman, Tara M; Elens, Iris; Harju, Erika; Kadan-Lottick, Nina S; Khor, Joel W T; Lemiere, Jurgen; Recklitis, Christopher J; et al.
Summary: Survivors of childhood, adolescent, and young adult (diagnosed when <25 years of age) cancer are at risk of mental health problems. The aim of this clinical practice guideline is to harmonise international recommendations for mental health surveillance in survivors of childhood, adolescent, and young adult cancer. This guideline was developed by a multidisciplinary panel of experts under the sponsorship of the International Guideline Harmonization Group. We evaluated concordance among existing survivorship clinical practice guidelines and conducted a systematic review following evidence-based methods. Of 7249 studies identified, 76 articles from 12 countries met the inclusion criteria. Recommendations were formulated on the basis of identified evidence in combination with clinical considerations. This international clinical practice guideline strongly recommends mental health surveillance for all survivors of childhood, adolescent, and young adult cancers at every follow-up visit and prompt referral to mental health specialists when problems are identified. Overall, the recommendations reflect the necessity of mental health surveillance as part of comprehensive survivor-focused health care.